Poly- and per-fluoroalkyl compounds in sediments of the Laurentian Great Lakes: Loadings, temporal trends, and sources determined by positive matrix factorization. (December 2019) - Christensen, Erik R.; Zhang, Ruijie; Codling, Garry; Giesy, John P.; Li, An
Abstract: A recent data set for 22 poly- and per-fluorinated compounds (PFASs) in Ponar grab samples of surface sediments and cores from the Great Lakes of North America was examined for concentrations, loads, correlations with geographical coordinates and depth (time), and for sources. Correlations were determined by multivariate regression analyses. Source apportionment of PFASs was carried out by positive matrix factorization (PMF) for two cores from Lake Ontario. For the five lakes together, the total load of PFASs in sediments was estimated to be 245 ± 24 tonnes, which is about half the load for total PCBs. The recent annual loading was 1812 ± 320 kg/yr. Concentrations and inventories of PFASs were greatest in Lakes Erie and Ontario. Since 1947, concentrations of perfluorooctane sulfonic acid (PFOS) in ten cores have increased exponentially as a function of time with doubling times between 10 and 54 yr and have leveled off in three cores since 2000. PMF demonstrated an effective grouping of two particle-associated factors, characterized mainly by longer-chain PFASs (C ≥ 8) and two other factors of mainly shorter-chain compounds (C ≤ 6). Two factors feature only one dominant compound: factor 1, PFOS, and factor 3, perfluorobutane sulfonic acid (PFBS). Of all factors, factor 3 with PFBS has the largest contribution (47.8%). Significant scores for perfluorohexane sulfonic acid (PFHxS) and PFBS, along with flat or decreasing PFOS contributions since 2003, indicate that the replacement of PFOS with these compounds is beginning to take effect in the environment. Graphical abstract: Image 1 Highlights: The total load of 22 PFASs in Great Lakes sediments is estimated to be 245 ± 24 tonnes. PFOS input doubles every 10–54 years and has leveled off at three sites since 2000. Some short-chain PFASs were found in sediment deposited before their production began. There are four PMF factors, two for shorter-chain and two for longer-chain PFASs. PMF results agree with the partitioning behavior expected based on Koc.